2019
DOI: 10.3390/ma12233967
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Glass-Based Endodontic Sealer as a Promising Root Canal Filling Material without Semisolid Core Materials

Abstract: Endodontic treatment for a tooth with damaged dental pulp aims to both prevent and cure apical periodontitis. If the tooth is re-infected as a result of a poorly obturated root canal, periapical periodontitis may set-in due to invading bacteria. To both avoid any re-infection and improve the success rate of endodontic retreatment, a treated root canal should be three-dimensionally obturated with a biocompatible filling material. Recently, bioactive glass, one of the bioceramics, is focused on the research area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 73 publications
1
39
0
2
Order By: Relevance
“…Calcium silicate-based sealers, including more reactive calcium-silicate-based bioactive glass, known as bioactive root canal sealers, have been recently introduced [ 30 , 31 , 32 ]. Bioactive glass has been mainly used for dental hard tissue regeneration; however, it has also recently shown promise for the repair of several complex tissues [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Calcium silicate-based sealers, including more reactive calcium-silicate-based bioactive glass, known as bioactive root canal sealers, have been recently introduced [ 30 , 31 , 32 ]. Bioactive glass has been mainly used for dental hard tissue regeneration; however, it has also recently shown promise for the repair of several complex tissues [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have suggested that the conventional root canal sealers are easily dissolved [6] and have no dentinal adhesion [7]. Recently, bioceramics such as tricalcium silicate-, dicalcium silicate-, calcium phosphates-, colloidal silica-, or calcium hydroxide-based root canal sealers were developed [8,9]. The moisture within the dentinal tubules was utilized to solidify the calcium silicate hydrate phase [10].…”
Section: Synthesis Of Urethane-acrylate (Ua)mentioning
confidence: 99%
“…The antibacterial test was carried out by the following steps. First, colonies were added into 5 mL HBI broth, cultivated at 37 °C for 16-18 h. The medium of bacteria fluid of lysogeny broth (LB) was replaced by phosphate-buffered saline (PBS) by using the centrifugation for three times (8,000 xg, 3 min), and diluted to the concentration of 10 −5 -10 −7 (CFU/mL). Subsequently, the as-prepared suspension was spread onto the BHI agar plates (10 μL) and incubated cells at 37 °C for 16-18 h. The 0.5 McFarland (10 8 CFU/mL) bacterial fluid was produced by using E. faecalis (ATCC 29212).…”
Section: Antibacterial Testmentioning
confidence: 99%
“…Hydroxyapatite (HAp) is a more stable calcium phosphate with low solubility, being used as filler for composite resins, adhesive systems, and root canal sealers (4,5,6). Studies evaluating experimental endodontic sealers with HAp demonstrated biocompatibility in the animal model (7), presented bioactivity in vitro (8,9,10,11), and showed appropriate physicochemical properties as setting time, flow, solubility, microhardness, and bond strength (8,9,10,11).…”
Section: Introductionmentioning
confidence: 99%